Pilot study: Evaluation of potential drug-drug interactions in hospitalized pediatric patients - Fabiola Medina-Barajas; Estefanía Vázquez-Méndez; Edsaúl Emilio Pérez-Guerrero; Virginia Aleyda Sánchez-López; Iván I. Hernández-Cañaveral; Real-Ornelas Gabriel A; Selene G. Huerta-Olvera (Elsevier, 2020)
Purpose: Evaluate the type and severity of potential drug-drug interactions and identify risk factors involved, in pediatric patients admitted in a hospital setting. Methods: Transversal retrospective analytical study was carried out with hospitalized pediatric patients from a Hospital in the West of Mexico, second and third level. The patients included were ≤18 years old hospitalized in the children wards; those admitted at the emergency room, neonatal intermediate and intensive therapy units were not included. Medical prescriptions were reviewed taking into consideration anthropometric characteristics, diagnosis and number of drugs prescribed to identify potential drug-drug interactions using Micromedex 2.0 database. Results: 88 patients were included, an average of 4.6 ± 2.8 of drugs were prescribed per patient. 37 subjects (42%) presented some degree of potential drug-drug interactions of which 25.5% were major and 27.7% moderate according to the software. Identified risk factors were: age ≥ 4 years (OR 1.917; 95% CI 1.081-3.399), BSA ≥ 0.8m2(OR 1.825; 95% CI 1.021-3.263), height ≥ 1 m (OR 2.556;95% CI 1.322 - 4.941), and number of prescribed medications ≥ 4 (OR 2.106;95% CI 1.248 - 3.556). Conclusion: Some of the interactions found were for the benefit of the patient, but others were considered undesirable because they altered the pharmacokinetics of some of the medications administered. Detecting in time the harmful interactions for a patient may favor the patient's safety.